Availability of researcher-led eHealth tools for pain assessment and management: barriers, facilitators, costs, and design. (September 2018) - Higgins, Kristen S.; Tutelman, Perri R.; Chambers, Christine T.; Witteman, Holly O.; Barwick, Melanie; Corkum, Penny; Grant, Doris; Stinson, Jennifer N.; Lalloo, Chitra; Robins, Sue; Orji, Rita; Jordan, Isabel
Abstract : Abstract: Introduction: Numerous eHealth tools for pain assessment and management have been developed and evaluated with promising results regarding psychometric properties, efficacy, and effectiveness. Although considerable resources are spent on developing and evaluating these tools with the aim of increasing access to care, current evidence suggests they are not made available to end users, reducing their impact and creating potential research waste. Methods: This study consisted of 2 components: (1) a systematic review of eHealth tools for pediatric pain assessment and/or management published in the past 10 years, and (2) an online survey, completed by the authors of identified tools, of tool availability, perceived barriers or facilitators to availability, grant funding used, and a validated measure of user-centeredness of the design process (UCD-11). Results: Ninety articles (0.86% of citations screened) describing 53 tools met inclusion criteria. Twenty-six survey responses were completed (49.06%), 13 of which (50.00%) described available tools. Commonly endorsed facilitators of tool availability included researchers' beliefs in tool benefits to the target population and research community; barriers included lack of infrastructure and time. The average cost of each unavailable tool was 314, 425.31 USD (3, 144, 253.06 USD total, n = 10). Authors of available tools were more likely to have followed user-centered design principles and reported higher total funding. Conclusion: Systemic changes to academic and funding structures could better support eHealth tool availability and may reduce potential for research waste. User-centered design and implementation science methods could improve the availability of eHealth tools and should be further explored in future studies. Abstract : Supplemental Digital Content is Available in the Text.